The Development of Picture Books Based on Meaningful Learning to Increase Social Awareness of Elementary School Students - Normalasarie Normalasarie; Bunyamin Maftuh; Sapriya Sapriya (UIN Siber Syekh Nurjati Cirebon, 2024)
Abstract Instilling social care in children is essential to mitigate the negative impacts of globalization, which has contributed to declining empathy among students. This study aims to develop and evaluate the effectiveness of a picture book based on meaningful learning in enhancing elementary school students’ social care, particularly in the aspects of sharing and cooperation. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The independent variable was the use of the meaningful learning-based picture book, while the dependent variable was the students’ social care. The study was conducted on June 28–29, 2022, at Public Elementary School (SDN) Mandikapau Barat 2 Martapura, involving 20 students selected through purposive sampling. The results showed that in terms of knowledge, only 25% of students achieved mastery before the intervention, which increased to 100% after using the picture book. For social care, 55% of students reached mastery in sharing, and 70% in cooperation. These findings indicate that the meaningful learning-based picture book is effective in enhancing students' social care. This study offers a reference for teachers to adopt innovative learning media and serves as inspiration for developing similar educational materials.Keywords: meaningful learning, picture books, social care. AbstrakPenanaman karakter peduli sosial pada anak menjadi penting untuk mengurangi dampak negatif globalisasi yang ditandai dengan menurunnya empati. Penelitian ini bertujuan mengembangkan dan menguji efektivitas buku bergambar berbasis meaningful learning dalam meningkatkan kepedulian sosial siswa sekolah dasar, khususnya pada aspek berbagi dan bekerja sama. Metode yang digunakan adalah penelitian dan pengembangan (R&D) dengan model ADDIE yang mencakup tahap Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Variabel bebas dalam penelitian ini adalah penggunaan buku bergambar berbasis meaningful learning, sementara variabel terikatnya adalah kepedulian sosial siswa. Penelitian dilaksanakan pada 28–29 Juni 2022 di SDN Mandikapau Barat 2 Martapura dengan 20 siswa sebagai sampel yang dipilih melalui teknik purposive sampling. Hasil menunjukkan bahwa pada aspek pengetahuan, sebelum penggunaan buku bergambar hanya 25% siswa yang tuntas, meningkat menjadi 100% setelah intervensi. Pada aspek kepedulian sosial, indikator berbagi mencapai 55% tuntas dan bekerja sama mencapai 70% tuntas. Temuan ini menunjukkan bahwa buku bergambar berbasis meaningful learning efektif meningkatkan kepedulian sosial siswa. Penelitian ini memberikan referensi bagi guru dalam menggunakan media pembelajaran inovatif serta menjadi inspirasi bagi pengembangan bahan ajar serupa.Keywords: buku bergambar, pembelajaran bermakna, peduli sosial.